Development of highly bioactive long-acting recombinant porcine FSH for batch production management of sows - Jiawei Zhang; Lei Shi; Xiaorong Zhong; Yunhe Bai; Jun Dou; Lu Zhang; Xiaochao Shi; Bingchun Wu; Zemin Tan; Lin Yan; Jinku Yu; Jingru Zhang; et al. (Scientific Reports)
Abstract To improve the economic benefits, exogenous hormones are used to control follicular development and synchronize ovulation in the batch flow management of gilts and weaned sows. Equine chorionic gonadotropin (eCG) is widely used to stimulate follicular development in both experimental and farm animals. Despite its effectiveness, several side effects have been found, including the occurrence of follicular cysts, follicular premature luteinization, and increased follicular atresia. As eCG is a heterologous protein, the generation of antibodies has been found in the superovulation of cattle. Moreover, the extraction of eCG from pregnant mare serum raises concerns regarding animal welfare, as well as potential risks for disease transmission. Follicle stimulating hormone (FSH) controls the follicular growth and maturation in the porcine ovary under physiological conditions. In the current study, we developed a novel long-acting recombinant porcine FSH (rpFSH-pFc) consisting of porcine FSH and porcine fragment crystallizable (Fc) via (G4S)3 linker by using the available protein fusion technology to control the follicular development and maturation. The results of pharmacokinetic studies indicated that rpFSH-pFc exhibited a prolonged half-life in both rats and sows. The efficacy of rpFSH-pFc was confirmed by cAMP level evaluation and germinal vesicle breakdown (GVBD) analysis in vitro. Through ovarian weight gain, superovulation and fertility testing assays, our results revealed that a single rpFSH-pFc treatment could effectively promote follicular development and maturation in vivo. Meanwhile, the mRNA expression levels of the target genes associated with follicular development, maturation and ovulation were significantly up-regulated after rpFSH-pFc treatment. Taken together, our results revealed that rpFSH-pFc could bind to the FSH receptor, stimulate follicular growth and development in female mice, and possess a prolonged half-life in both rats and sows. These characteristics suggest that rpFSH-pFc may be an ideal candidate for promoting follicular growth and development in livestock production.